2021
DOI: 10.3390/cells11010078
|View full text |Cite
|
Sign up to set email alerts
|

The Role of LIM Kinase in the Male Urogenital System

Abstract: The LIM kinases (LIMK1 and LIMK2), known as downstream effectors, and the Rho-associated protein kinase (ROCK), a regulator of actin dynamics, have effects on a diverse set of cellular functions. The LIM kinases are involved in the function of the male urogenital system by smooth muscle contraction via phosphorylation of cofilin and subsequent actin cytoskeleton reorganization. Although LIMK1 and LIMK2 share sequence similarities as serine protein kinases, different tissue distribution patterns and distinct lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Roles of other proteins such as “optineurin”, a ubiquitin-binding adaptor protein; the “pregnancy zone protein”, a chaperone protein maintaining protein homeostasis during pregnancy, the “Programmed cell death 6-interacting protein” or “Testis, prostate and placenta-expressed protein” or “Maestro heat-like repeat family member 1” during spermatogenesis remain to be clarified. While for others, a role during spermatogenesis has been explored such as for prosaposin (PSAP) involved in the development of the reproductive system, cofilin as an actin depolymerizing factor, progranulin (PGRN) an acrosomal glycoprotein synthesized during spermatogenesis, centrin 3 a member of the centrosome protein family, or “Spermatogenesis-associated protein 6” (SPATA6) …”
Section: Resultsmentioning
confidence: 99%
“…Roles of other proteins such as “optineurin”, a ubiquitin-binding adaptor protein; the “pregnancy zone protein”, a chaperone protein maintaining protein homeostasis during pregnancy, the “Programmed cell death 6-interacting protein” or “Testis, prostate and placenta-expressed protein” or “Maestro heat-like repeat family member 1” during spermatogenesis remain to be clarified. While for others, a role during spermatogenesis has been explored such as for prosaposin (PSAP) involved in the development of the reproductive system, cofilin as an actin depolymerizing factor, progranulin (PGRN) an acrosomal glycoprotein synthesized during spermatogenesis, centrin 3 a member of the centrosome protein family, or “Spermatogenesis-associated protein 6” (SPATA6) …”
Section: Resultsmentioning
confidence: 99%
“…The primary features are promoting cell viability and suppressing cell adhesion 36 . LIMK1 which is one of the downstream molecules of the Rho family of small GTPases with their effector PAK1, is relevant in the migration invasion of prostate and breast cancers, osteosarcoma and other cancers 37–40 . A variety of recent researchers have found that a couple of various medicines, such as sea cucumber Cucumaria frondosa, could modulate cytoskeletal reconstruction through Rac1/PAK1/LIMK1 signaling axis, thereby suppressing the adhesion and migration of neoplastic cells 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Urethral stricture is characterized by fibrotic changes ( Figure 1a ), and common pathological features of urethral stricture include excessive fibroblast proliferation, extracellular matrix (ECM) abnormalities, and collagen synthesis within the urethral spongiosa. 18 Among these, ECM abnormalities feature changes in the composition of glycosaminoglycans, 19 accumulation of transforming growth factor-β (TGF-β), and dysregulation of collagen deposition and collagen maturation. 20 It is now understood that collagen I and III are the main components of the ECM, and the higher percentage of type I/III in the lumen of urethral stricture than that in the normal urethral lumen account for the poor compliance of urethral stricture scar tissue fibrosis.…”
Section: Pathophysiology Of Urethral Stricturementioning
confidence: 99%